Economic growth assessment through an ARDL approach: The case of African OPEC countries. (December 2020) - Moutinho, Victor; Madaleno, Mara
Abstract: A new time series model is proposed, allowing to test the hypotheses of neutrality, conservation, growth, or feedback hypothesis for a group of African countries included in OPEC (Algeria, Nigeria, Libya, Equatorial Guinea, Gabon, and Angola). The Autoregressive Distributed Lags (ARDL) unrestricted Error Correction Model (ECM) approach for the period of 1973–2017 is applied for this purpose. This allows us to examine the short and long-run dynamic impact of energy consumption, oil prices, trade openness, and urbanization on economic growth. Long-run results point to a positive impact of urbanization over GDP in only two countries, being negative in the other two. Oil price impact is positive over GDP in three of them, whereas trade openness drives positively GDP in Equatorial Guinea and Angola, while negatively in Algeria. Heterogeneous bidirectional causality is found for countries and variables. As well, short-run results are also country dependent. The bidirectional causalities findings highlight that variables can predict each other in the future and policymakers should be aware of this, especially accounting for results and sample heterogeneity. Results seem to validate the neutrality hypothesis, considering energy consumption and GDP.